Developments of Corey-Fuchs Reaction in Organic and Total Synthesis of Natural Products - M. Heravi, Majid; Asadi, Shima; Nazari, Niousha; Malekzadeh Lashkariani, Boshra (Current Organic Chemistry, 2015)
Corey-Fuchs olefination is a two-step reaction, involving the reaction of an aldehyde and tetrabromomethane (CBr4) in the presence of the triphenylphosphine (Ph3P) to synthesize 1,1-dibromoolefins. In the second step, the conversion of the dibromoolefins to alkynes occurred in the presence of n-BuLi as the base. This transformation was first discovered by E. J. Corey and P. L. Fuchs in 1972. Due to the importance of terminal alkynes in the synthetic organic chemistry, the Corey-Fuchs reaction has found many applications in organic transformations; particularly in the total synthesis of several biologically active natural products, often as starting materials.
Keywords: 1-Dibromoolefins